P602 Vedolizumab subcutaneous influencing disease course in Constant-care app solution. (27th May 2021) - Nørgaard, J; Malte, R; Charlotte, P L; Mette, B; Eva, F; Petra, W; Dorit, A; Lotte, S; Johan, B; Pia, M
Abstract: Background: The Constant-care app solution (CC) has been shown to empower patients with mild-moderate Ulcerative Colitis (UC) in 5-ASA treatment and improve disease specific quality of life (1) . Here we present preliminary data on our study to investigate the effects of CC on quality of life in patients with moderate-severe UC or Crohns Disease (CD) treated with s.c.vedolizumab, launched in June 2020 in Denmark. Methods: The study is an ongoing non-interventional, observational study. Patients are homemonitored via CC for 24 months. CC shows data on patient's disease status, grouping them into three: green (remission), yellow (worsening), red (severe disease). Patients were recruited from the outpatient clinic at the Department of Gastroenterology, North Zealand University Hospital, Greater Copenhagen. Simple Clinical Colitis Index (SCCAI), Harvey-Bradshaw Index (HB-I), Fecal calprotectin (FC) and short QoL (0–70) are measured every two months or during a flare up between fixed screenings. Serious adverse events (SAE) and adverse events (AE) are monitored. Results: 19 patients out of 40 have been included, 8 with CD and 11 with UC. None experienced SAEs. Five experienced AEs, of which four discontinued treatment. One patient experienced treatment failure during this study. Of the 15 patients, two are in complete remission, (Q2 respectively Q3). Five of the remaining patients have not entered more than two data entries in CC (data not shown).All patients sustained remission based on FC, except for two data points for two individual patients. Good QoL ≥ 50 was almost unchanged for 6 patients. Conclusion: IBD CC has proven a usefull tool for surveillance and maintenance of remission in IBD patients treated with s.c. vedolizumab. S.c. vedolizumab has in this patientgroup, shown to provide sustainable QoL, sustained remission, and to have few AEs. 1) Elkjaer M, Shuhaibar M, Burisch J, Bailey Y, Scherfig H, Laugesen B, et al. E-health empowers patients with ulcerative colitis: a randomised controlled trial of the web-guided 'Constant-care' approach. Gut. 2010;59(12):1652–61.